Handbook of applied cryptography - Menezes, A. J. (Alfred J.) 1965-; Van Oorschot, Paul C.; Vanstone, Scott A. (Discrete mathematics and its applications, 1997)
Cryptography, particularly public-key cryptography, has emerged in the last 20 years as a serious discipline. This handbook serves an introduction to the more practical aspects of both conventional and public-key cryptography.